VIOLENCE THROUGH THE EYES OF YOUTH: A PHOTOVOICE EXPLORATION. Issue 1 (13th December 2012) - Chonody, Jill; Ferman, Barbara; Amitrani‐Welsh, Jill; Martin, Travis
<x xml:space="preserve">Abstract</x> In 2001 the CDC declared youth violence a public health issue. In summer 2008, we embarked on a project designed to explore the issue of violence from the standpoint of youth who are exposed to and affected by violence in their communities. Using photovoice as the primary methodology, the project sought to develop a more nuanced and deeper understanding of these issues, while simultaneously giving youth a voice and further developing their critical thinking skills. Digital images produced by the youth and the subsequent structured conversations focused on representations of violence, causes of violence and ways to address violence. Analyses of the images and conversations, especially in the context of the literatures on youth violence, race and poverty, support the utility of photovoice as a tool for understanding how youth perceive violence and underscore the need to listen to the voices of those affected by violence.